Evaluating interactive e-module for contextual teaching and learning linear equation in one variable - Rachmawati, Lina; Rusmining, Rusmining (Bulletin of Applied Mathematics and Mathematics Education, 2023)
This research is motivated by the lack of teaching materials used in the mathematics learning process. On the other hand, students still struggle to solve story problems related to contextual issues. Therefore, this research aims to develop a product in the form of an interactive E-Module based on Contextual Teaching and Learning (CTL) for 7th-grade students and to evaluate the validity and practicality of the product. This type of research is developmental research using the ADDIE research model (Analyze, Design, Development, Implementation, & Evaluation). The results of the research show that the assessment of the interactive E-Module obtained an average score of 3.68 by subject matter experts with a category of very valid and an average of 3.6 by media experts with a category of very valid. Meanwhile, for student responses, it obtained a percentage of 90.72% in the small-scale trial with very practical criteria and a percentage of 85.95% with very practical criteria in the large-scale trial. Based on these results, it can be concluded that the interactive e-module based on CTL is strongly valid and very practical, making it suitable for use in learning.